On the influence of small chemical changes upon the supramolecular association in substituted 2-(phenoxy)-1,4-naphthoquinones - Tonin, Marlon D. L.; Garden, Simon J.; Jotani, Mukesh M.; Wardell, James L.; Tiekink, Edward R. T. * (Oldenbourg Wissenschaftsverlag, 2019)
X-ray crystallography reveals the common feature of the title compounds is a 1,4-naphthoquinone ring system with a substituted phenoxy residue adjacent to an oxo-group to give 1 (H), 2 (3-Br), 3 (3-CF3), 4 (4-CN) and 5 (4-NO2). To a first approximation the fused ring system along with the two oxo substituents is planar with the major difference between the molecules relating to the relative orientations of the pendant phenoxy residues: dihedral angles range from 56.56(4)° (3) to 87.52(10)° (2). The presence of intermolecular C‒H…O interactions is the common feature of the supramolecular association in the crystals of 1-5. In each of 1 and 5, these extend in three-dimensions but, only to supramolecular dimers in 4, chains in 2 and layers in 3. Each crystal also features C=O…π interactions, pointing to the importance of these points of contact in this series di-oxocompounds. In 2, these, along with C‒Br…π interactions lead to a threedimensional architecture. For 3, the C=O…π and π…π interactions occur within the layers which stack without directional interactions between them. In 4, C‒H…O and C=O…π interactions combine to give a supramolecular layer, which also stack without directional interactions in the interlayer region. Further analysis of the molecular packing was conducted by a Hirshfeld surface analysis (HSA). This points to the significant role of H…H, C…H/H…C and O…H/H…O contacts in the packing of 1. Notably different roles for these contacts are found in the other crystals correlating with the participation of the respective substituents in the molecular packing. The HSA suggests the association between layers in 3 (weak F…F and H…F interactions) and 4 (weak H…N interactions) is contributed by the phenoxy-substituents.